Tetrameric Neuraminidase of Influenza A Virus Is Required to Induce Protective Antibody Responses in Mice - Deng, Xiren; Wang, Qimin; Liu, Mei; Zheng, Qinwen; Wu, Fan; Huang, Jinghe (Frontiers in Microbiology, 2021)
Influenza neuraminidase (NA) is able to induce cross-subtype immunity and is considered as a promising target for development of universal influenza vaccines. However, commercial influenza vaccines only induced low NA-specific immune responses due to low amounts and denatured conformation of NA proteins in current inactivated or split influenza vaccines. Here, we investigated the protective efficacy of recombinant tetrameric and monomeric NA proteins to determine whether the conformation contributed to induce protective immunity. We found that H1N1PR8NA tetramer (NAtet) could provide complete homologous protection against A/PR8 (H1N1) virus infection in mice, while the protection of H1N1PR8NA monomer (NAmono) was moderate. Higher levels of NA-reactive binding- and inhibition- antibodies and less weight loss were observed in H1N1PR8NAtet vaccinated group. Similarly, H5N1VNNAtet immunization exhibited preferable heterologous protection than H5N1VNNAmono, but neither H7N9SHNAtet nor H7N9SHNAmono vaccination showed heterosubtypic protection. We also compared the effect of three adjuvants, aluminum, 3’3’-cGAMP (cGAMP), and Poly(I:C), on the humoral response and protective efficacy induced by H1N1PR8NAtet. H1N1PR8NAtet protein adjuvanted with aluminum was observed to exhibited better capacity in inducing NA-specific humoral immunity and preventing weight loss than with cGAMP or Poly(I:C). In conclusion, our data demonstrate that tetrameric NA with natural conformation is required to induce protective anti-NA immunity. NA tetramer could provide homologous protection and subtype-specific cross-protection. In addition, aluminum adjuvant is preferable in recombinant NA protein vaccination.